A organização do espaço agrário e as políticas agrícolas no município de Simão Dias (SE) - Santos, Luciano Ricardio de Santana (2008)
This study investigate the process for Agricultural Policy on Agricultural Space. Thus extols is the understanding about the changes arising from the introduction, in the Agricultural Space, new actions and new objects that provide a continuity of the expropriator logic of capitalism on the socio-spatial structure. The new actions and new objects in the space created by Public Policy Agrarian increase the duality between Capital and Space. Additionally, the actions and objects new insert a new opposite dynamic on the family farming strutucture, that is based on the replacement of traditional agricultural practices by practicing modern and specialized capitalist farming. The Agricultural Space organization form in Simão Dias city, with the introduction of Agriculture inefficient, shows clearly the modern logic capitalist in which stimulates productivity, unclearly the social-spatial structure through new actions and new foreign objects in the order of space and production of traditional forms of farming community, simãodiense family farmers. The new actions and new objects rival with the objects and actions created by the previous form of family farming, causing the extinction of local agricultural knowledge and enabling the introduction of commercial logic of the capitalist production structure and social-space of simãodiense agrarian farming.